Physics of Seismo-electromagnetic Phenomena - Silva, Hugo Gonçalves (2012)
The seismo-electromagnetic phenomena (SEMG) are integrated in a relatively recent research field that studies diverse phenomena such as: unusual seismo-electrical signals [1], abnormal ultra-low-frequency (ULF) seismo-electromagnetic emissions [2], very-low-frequency (VLF) and low-frequency (LF) radiobroadcast anomalies associated with ionosphere perturbations [3], variation of total electron content of the ionosphere [4], and atypical infrared emissions [5], all related with the preparatory stage of impending earthquakes. In the past, like many other branches of science like Quantum Mechanics, SEMG have been responsible for intense debates about its credibility, in this case concerning its applicability to short-term earthquake prediction [6]. In fact, the development of a truly pre-quake forecasting system is still an elusive plan, but SEM emissions are now a very well established effect extensively reported in literature. Nevertheless, much of the Physics implicated is still not fully understood. Thus, our main effort is directed towards a systematic field observation of SEMG effects and the development of both constructive theoretical models and laboratorial experiments to promote a better understanding of the Physics engaged in these phenomena. In this presentation we will present a sum up of our recent achievements [7,8,9], focusing future work and improvements. [1] A. Konstantaras, et al., On the electric field transient anomaly observed at the time of the Kythira M=6.9 earthquake on January 2006, Nat. Hazards Earth Syst. Sci. 7, 677 (2007). [2] T. Bleier, et al., Investigation of ULF magnetic pulsations, air conductivity changes, and infra red signatures associated with the 30 October Alum Rock M5.4 earthquake, Nat. Hazards Earth Syst. Sci. 9, 585 (2009). [3] P. Biagi, et al., An overview on preseismic anomalies in LF radio signals revealed in Italy by wavelet analysis, Annals of Geophysics 51, 237 (2008). [4] V. Chauhan, et al., Ultra-low-frequency (ULF) and total electron content (TEC) anomalies observed at Agra and their association with regional earthquakes, Journal of Geodynamics 48, 68 (2009). [5] D. Ouzounov, et al., Outgoing long wave radiation variability from IR satellite data prior to major earthquakes, Tectonophysics 431, 211 (2007). [6] S. Uyeda, et al., Short-term earthquake prediction: Current status of seismo-electromagnetics, Tectonophysics 470, 205 (2009). [7] H.G. Silva, et al., Atmospheric electrical field anomalies associated with seismic activity, Nat. Hazards Earth Syst. Sci. 11, 987 (2011). [8] H. G. Silva, et al., Electric transport in different granitic rocks, EGU General Assembly 2011 (EGU 2011), 3-8 April 2011, Vienna (Austria). [9] H.G. Silva, et al., Piezoelectric effect during solid fracture causing electromagnetic emissions, International Conference on Computational Modelling of Fracture and Failure (CFRAC 2011), 6-8 June 2011, Barcelona (Spain).